Моделювання RESTFUL API для системи автоматизації приватних електронних закупівель - Дорошенко, А.Ю.; Бодак, Б.В. (Проблеми програмування, 2021)
Розроблено програмний засіб для автоматизації електронних закупівель на основі .NET Core RESTful API з використанням специфікацій OpenAPI v3.0. Реалізовано авторизацію користувачів системи, постачальників та замовників, за допомогою відкритого стандарту OAuth та Microsoft Identity Server. Для скорочення часу відгуку системи здійснено кешування даних на рівні репозиторію за підтримки розподіленного кешу. Створено підсистему для обробки та переходу між станами закупівель на основі скінченного автомату станів. Проведено випробування розробленого програмного засобу з використанням модульних та інтеграційних тестів. The software for the e-procurement system was developed based on .NET Core RESTful API with Open API specifications. The server side uses RESTful API which ensures compatibility with the majority of clients and enables them to exchange information in JSON format. The authentication and authorization flow was implemented using OAuth open standard paired with Microsoft Identity Service. User roles and functionality were handled with a standalone service for authentication and registration that made our system efficient and scalable. Business logic was designed to be split into micro-services accessible through routing controllers. This approach allowed us to separate the responsibilities between the server and the client side. Special authorization headers passed during modification queries allowed us to control and restrict access to particular resources for unauthorized users. The distributed cache mechanism inside the data repository level was used in order to increase the responsiveness of the system. The state handling subsystem was designed utilizing Finite State Machine concepts. The developed system was verified using unit and integration tests.